Synthesis and characterization of surfmers for latex stabilization in RAFT-mediated miniemulsion polymerization - Matahwa, Howard (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2005.